A Review of Mixed-Income and Equitable Transit-Oriented Development - Correia, Rebecca; Sunil, Maria; Sax, Aislyn; MacPherson, Eric; Gravely, Evan (Prepared by the McMaster Research Shop for the Hamilton Community Land Trust, 2022)
The Hamilton Community Land Trust (HCLT) is a non-profit organization that advocates for inclusive and equitable forms of development, and the sustainable ownership of land for community benefit. The HCLT partnered with the McMaster Research Shop to better understand how concepts like mixed-income (MID) and equitable transit-oriented development (eTOD) can inform LRT development plans. To do this, the Research Shop team selectively reviewed literature to understand the principles of MID and eTOD, reviewed LRT development plans for gaps where these principles could be applied, and then identified opportunities for Hamilton's LRT project. This report outlines our findings.
Keywords: Hamilton, community-engaged research, LRT, mixed-income development, equitable transit-oriented development